The effect of training order on neuromuscular, endocrine and mood response to small-sided games and resistance training sessions over a 24-h period - William Sparkes (Journal of Science and Medicine in Sport, 2020)
ObjectivesThis study examined the acute effect of small-sided-game (SSG) and resistance training sequence on neuromuscular, endocrine and mood response over a 24-h (h) period.DesignRepeated measures.MethodsFourteen semi-professional soccer players performed SSG-training (4vs4 + goalkeepers; 6 × 7-min, 2-min inter-set recovery) followed by resistance training 2 h later (back-squat, Romanian deadlift, barbell-hip-thrust; 4 × 4 repetitions, 4-min inter-set recovery; 85% 1 rep-max) (SSG + RES), and on a separate week reversed the session order (RES + SSG). Physical demands of SSG’s were monitored using global positioning systems (GPS) and ratings of perceived exertion (RPE). Countermovement-jump (CMJ; peak power output; jump height) and brief assessment of mood were collected before (pre), during (0 h) and after (+24 h) both protocols. Salivary testosterone and cortisol concentrations were obtained at the same time-points but with the inclusion of a measure immediately prior to the second training session (+2 h).ResultsGPS outputs and RPE were similar between SSG-training during both protocols. Between-protocol comparisons revealed no significant differences at +24 h in CMJ performance, mood, and endocrine markers. Testosterone was higher at 0 h during RES + SSG in comparison to SSG + RES (moderate-effect; +21.4 ± 26.7 pg ml−1; p = 0.010), yet was similar between protocols by +2 h.ConclusionsThe order of SSG and resistance training does not appear to influence the physical demands of SSG’s with sufficient recovery between two sessions performed on the same day. Session order did not influence neuromuscular, endocrine or mood responses at +24 h, however a favourable testosterone response from the resistance first session may enhance neuromuscular performance in the second session of the day.